Distribution Logistics Advanced Solutions to Practical Problems - Fleischmann, Bernhard; Klose, Andreas (Lecture Notes in Economics and Mathematical Systems,, 2005)
The complexity of distribution systems is augmented by various trends: globalization of the manufacturing industry, rising customer demands, and the reverse flows within closed-loop systems. In this light, the need for 'advanced' planning methods that are based on quantitative optimization is constantly increasing. This book takes up the challenges posed by these developments. In doing so, it presents recent results and case studies from a group of researchers that regularly meet at the IWDL (International Workshop on Distribution Logistics). The text covers the design of distribution networks, vehicle routing, warehousing and reverse logistics. It also contains a comprehensive review of more than 60 case studies in reverse logistics.